Coagulation and complement: Key innate defense participants in a seamless web - Pryzdial, Edward L. G.; Leatherdale, Alexander; Conway, Edward M. (Frontiers in Immunology, 2022)
In 1969, Dr. Oscar Ratnoff, a pioneer in delineating the mechanisms by which coagulation is activated [1] and complement is regulated [2], wrote, "In the study of biological processes, the accumulation of information is often accelerated by a narrow point of view. The fastest way to investigate the body’s defenses against injury is to look individually at such isolated questions as how the blood clots or how complement works. We must constantly remind ourselves that such distinctions are man-made. In life, as in the legal cliché, the devices through which the body protects itself form a seamless web, unwrinkled by our artificialities." [3] Our aim in this review, is to highlight the critical molecular and cellular interactions between coagulation and complement, and how these two major component proteolytic pathways contribute to the seamless web of innate mechanisms that the body uses to protect itself from injury, invading pathogens and foreign surfaces.